Simultaneous Gradual Correction of Bilateral Late Onset Tibia Vara using High Tibial Osteotomy with a Mono-Axis Dynamic External Fixator: A Case Report - Triharto Banjaran Sakti; Natan Kevin Partogu Siagian; Wongso Kesuma; Andreas Marojahan Haratua Siagian (Indonesian Hip and Knee Society (IHKS), 2022)
Tibia vara is a disease characterized by an abrupt angulation of the tibia into varus in the proximal end. This condition is caused by developmental growth defect of the proximal tibia physis. Tibia Vara can be classified into groups according to the age of the patient and the mainstay treatment is either acute or gradual surgical correction.A 21 year-old man with chief complaint bowing of the legs with leg pain since 3 years ago. Physical examination showed bilateral genu varum. The anteroposterior long leg standing X-Ray found that the deformity was of osseous origin at the proximal part of the tibia in varus position. Medial osteotomy of the proximal tibia was performed and a dynamic external fixator was installed. Gradual correction was performed at a rate of 1 mm per day. After 3 months, radiological evaluation showed good union and target angle of correction with acceptable mechanical axis was achieved. Patient had no complaint of pain or instability post-surgery.Gradual correction using external fixator provides a more flexible angle correction with lower risk of neurovascular compromises; but with its own disadvantage such as loss of correction after removal of the external device. In this case, gradual correction of late onset tibia vara using dynamic external fixator provides satisfactory outcome and enable a more fine-tuned angle correction. It also potentially eliminate the need for a second surgery to remove the external device; thus reducing the length of hospitalization.